The Effect Of Trustworthiness, Expertise, Attractiveness, And Online Customer Review On Purchase Intention In Madiun - Khamima Nurizzah; Hendra Setiawan; Sulthan Misbahul Ghifaari (Cita Konsultindo Research Center, 2026)
This study aims to empirically examine the influence of trustworthiness, expertise, attractiveness, and online customer review on consumers’ purchase intention in culinary products within the Madiun area, with a case study on TikTok followers of @tio_philus. The research employed a quantitative method with a sample of 384 TikTok users residing in Madiun who interact with the @tio_philus account. The research instrument was a questionnaire distributed online via Google Form and measured using a Likert scale. The data analysis technique used was multiple linear regression analysis with the assistance of SPSS software. The findings of this study indicate that: (a) Trustworthiness has a positive and significant effect on consumers’ purchase intention, (b) Expertise has a positive and significant effect on consumers’ purchase intention, (c) Attractiveness has a positive and significant effect on consumers’ purchase intention, and (d) Online Customer Review has a positive and significant effect on consumers’ purchase intention toward culinary products promoted by @tio_philus through TikTok in the Madiun area.